The Effect Of Financial Distress And Disclosure On Going Concern Opinion Of The Banking Company Listing In Indonesian Stock Exchange (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to determine the effect of financial distress and disclosure to the going concern of banking companies listing on Indonesia Stock Exchange. Population of this research is all banking companies listed in Indonesian Stock Exchange. Sample in this research is 6 banking companies. The analysis method is logistic regression. The result of the research shows that financial distress has a negative effect on going-concern opinion, while disclosure negatively affect of going concern opinion on banking company listing in Indonesian Stock Exchange.